Africa agriculture transformation scorecard performance and lessons for Zimbabwe - Makotose, W.; Mayoyo, A.; Nicholas, G.; Nhemachena, Charles; Matchaya, Greenwell C.; Nhlengethwa, Sibusiso (Regional Strategic Analysis and Knowledge Support System for Southern Africa, 2019)
The main objective of this BR brief is to summarize the performance, key issues, and recommendations for improving progress toward agricultural transformation in Zimbabwe. This brief provides recommendations and action items based on Zimbabwe’s performance in the inaugural BR mechanism to help the country improve its domestication and implementation of the Malabo Declaration commitments. In addition, recommendations are shared to help the country strengthen mutual accountability to actions and results, ultimately contributing to improving the country’s progress towards achieving the Malabo targets by 2025.